2018
DOI: 10.2217/bmm-2017-0372
|View full text |Cite
|
Sign up to set email alerts
|

Thiol/Disulphide Homeostasis in Thoracic Aortic Aneurysm and Acute Aortic Syndrome

Abstract: Lower thiol levels may be associated with the higher risk of aortic aneurysm development and may increase after surgical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…In a recent study published by Akkuş et al, the native thiol and the total thiol levels were demonstrated to correlate moderately with maximal aortic diameter. The total thiol level was also found to be an independent predictor of maximal aortic diameter in this study, and it was observed that the thiol levels increased after surgical repair of the aorta [1]. Likewise, the total and native thiol levels were lower in the patients with AAD in our study.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In a recent study published by Akkuş et al, the native thiol and the total thiol levels were demonstrated to correlate moderately with maximal aortic diameter. The total thiol level was also found to be an independent predictor of maximal aortic diameter in this study, and it was observed that the thiol levels increased after surgical repair of the aorta [1]. Likewise, the total and native thiol levels were lower in the patients with AAD in our study.…”
Section: Discussionsupporting
confidence: 79%
“…As it is a clinically silent disease, it is difficult to assess the true prevalence and incidence of aortic aneurysms. Aortic aneurysms are associated with a rupture risk of more than 5% per year resulting in death [1]. Several mechanisms have been shown to be linked with the development of AAD such as hemodynamic force, destructive remodeling of the extracellular matrix, familial predisposition, transmural inflammation of the aorta, and oxidative stress [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Authors have concluded that thiol and disulfide levels are distinctive tests between healthy subjects and aneurysm or acute aortic syndrome [121].…”
Section: Other Disordersmentioning
confidence: 99%
“…Beyond traditional risk factors for aortic aneurysms such as advanced age, HT and smoking; matrix metalloproteinases (MMPs) and ROS are also considered to be important risk factors in the pathophysiology of AAD (24). In a study published by Akkus et al (2), native thiol and total thiol levels were demonstrated to be correlated with maximal aortic diameter. Total thiol level was also found to be an independent predictor of maximal aortic diameter in this study, and that thiol levels increased after surgical repair of the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…The enlargement of the ascending aorta is defined as aneurysm if it is over the one and a half times the normal diameter. Aortic aneurysm is associated with more than 5% rupture risk per year resulting with death (2). Several local and/or systemic factors have pivotal roles in the pathogenesis of AAD such as increased age, smoking, male gender, familial genetic factors, hemodynamic alterations, inflammation of the aorta, and destructive remodeling of the extracellular matrix (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%